2022
DOI: 10.32672/jse.v7i4.4956
|View full text |Cite
|
Sign up to set email alerts
|

Preparasi dan Karakteristik Lembaran Plastik Limbah Masker Berdasarkan Variasi Lapisan Luar, Tengah, dan Dalam

Abstract: Peningkatan konsumsi pengunaan masker di tingkat rumah tangga sebagai salah satu alat pelindung diri (APD) berdampak pada limbah yang dihasilkan. Bahan masker sekali pakai adalah polipropilena yang merupakan plastik dengan sifat yang sulit terurai dan membutuhkan waktu lama untuk terurai di lingkungan. Sehingga proses daur ulang menjadi salah satu cara yang dapat dilakukan untuk mengurangi dampak lingkungan yang ditimbulkan. Pada daur ulang masker mengunakan metode hot press dengan suhu 200°C, tekanan 100 bar,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Polypropylene is the main material used to produce disposable masks (Selvaranjan et al, 2021). This is in accordance with the observations made by Rebia et al (2022), functional groups of three-layer mask waste were confirmed and analyzed using a Nicolet™ iS50 Fourier Transform Infra-Red Spectroscopy (FTIR) Spectrometer. Based on the results of the functional group analysis, the outer (L), middle (T), and inner (D) layer masks (Figure 2) are characterized by the typical absorption of polypropylene.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Polypropylene is the main material used to produce disposable masks (Selvaranjan et al, 2021). This is in accordance with the observations made by Rebia et al (2022), functional groups of three-layer mask waste were confirmed and analyzed using a Nicolet™ iS50 Fourier Transform Infra-Red Spectroscopy (FTIR) Spectrometer. Based on the results of the functional group analysis, the outer (L), middle (T), and inner (D) layer masks (Figure 2) are characterized by the typical absorption of polypropylene.…”
Section: Resultssupporting
confidence: 81%
“…Figure 3. FTIR results on functional group analysis of disposable mask waste layers (Rebia et al, 2022) Polypropylene is a vinyl polymer in which each carbon atom is attached to a methyl group (-CH3) (Figure 4). Polypropylene is a type of plastic that is often used in various industries because it is very cheap, has a low density that makes it easy to print, and has excellent chemical resistance (Hisham, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The middle layer medical mask was chosen because it is made of the strongest polypropylene layer, as opposed to the first and third layers, which are suitable for composite materials. It was known that the mask was made of polypropylene as the result of an FTIR investigation from the earlier study conducted by the researcher [13]. After being cut, the mask material was put into a grinder for a maximum of 10-15 grams to be smoothed evenly to produce reinforcement in the form of particles.…”
Section: Preparation Process For Making Composite Samplesmentioning
confidence: 99%
“…10% of polypropylene had the highest tensile strength compared to 30% and 50%, with 90-100 MPa, while the percentage of 50% of polypropylene fiber and epoxy in another study obtained 28 MPa of tensile strength [12]. The earlier studies also used waste from medical masks to calculate the mechanical properties of a thin layer of polypropylene sheet [13], [14]. On the other hand, there aren't many composite samples that have been investigated with the raw materials from medical mask waste.…”
Section: Introductionmentioning
confidence: 99%